A relação entre o comportamento higiênico e o ácaro Varroa destructor em colônia de abelhas produzindo de geléia real e mel - Wielewski, Priscila (2010)
Genetic and phenotypic parameters for hygienic behavior, invasion and infestation rates of Varroa destructor in Africanized honeybee colonies were analyzed. The hygienic behavior, invasion and infestation rates, total reproduction and effective reproduction of Varroa destructor in colonies producing honey (20 hives) or royal jelly (30 hives) were evaluated. It was verified the fixed effects significance of month, type of product (honey and royal jelly), and its interactions, using the procedure of generalized linear models. To estimate the covariances, it was made a routine using the software Winbugs (Bayesian inference Using Gibbs Sampling) with Bayesian inference. The averages for colonies producing honey or royal jelly, respectively, were: hygienic behavior in 24 hours 74.38 and 71.40%; infestation rates 8.30 and 11.40%; invasion rates 9.50 and 7.50%; total reproduction 102.40 and 54.60% and effective reproduction 62.00 and 33.00%. The addictive genetic variances for invasion rate (0.16), total reproduction (0.25) and effective reproduction (0.94) of the mite were highest than estimates for hygienic behavior in 24 hours (0.05) and infestation rate (0.04). The mean heritability for hygienic behavior, infestation and invasion rates, total reproduction and effective reproduction of the mite were 0.58, 0.54, 0.56, 0.63 and 0.61, respectively. The genetic correlation of -0.48 found for hygienic behavior characteristics with total reproductive rate of the Varroa destructor shows that the hygienic behavior may be considered the most interesting feature for selection, as well as presenting the heritability of high magnitude, when combined with total reproduction rate of the destructor has a high correlation and antagonistic, so in cases of high infestation of the Varroa destructor, selecting for hygienic behavior would decrease the rate of reproduction rate of the destructor.